Local Pastry Production: Empowering Economic Growth through Pia Cake Industry: Produksi Kue Lokal: Pemberdayaan Pertumbuhan Ekonomi melalui Industri Kue Pia - Yusuf, Lisa Aprilia; Agustina, Isna Fitria (Indonesian Journal of Innovation Studies, 2023)
This qualitative descriptive study investigates economic empowerment in Kampung Pia, located in Kejapanan Village, through the lens of pastry sales, particularly the renowned pia cake. Employing purposive sampling, data collection methods include interviews, observations, documentation, and literature review. The Miles and Huberman data analysis approach, comprising data collection, reduction, presentation, and conclusion drawing, was utilized. The research reveals a concentrated workforce exclusively involved in pia cake production. This study contributes valuable insights into the localized economic impact of specialty pastry production, providing a basis for further research and potential development strategies for similar communities worldwide. Highlights: Localized Economic Impact: The study sheds light on the focused economic contributions of a specialized local industry, emphasizing the significance of micro-enterprises in community development. Purposive Sampling Method: Employing a purposive sampling technique, the research ensures targeted participant selection, providing depth and relevance to the qualitative analysis of economic empowerment. Global Relevance of Pastry Production: Insights from this study extend beyond Kejapanan Village, offering a basis for understanding and developing localized pastry industries worldwide, fostering global perspectives on community economic empowerment. Keywords: Economic Empowerment, Pia Cake Industry, Localized Entrepreneurship, Qualitative Research, Community Development.